Purification of Flake Graphite in a Certain Area of Madagascar - Zhenmin ZHAI; Yangshuai QIU; Lingyan ZHANG; Zhenfei MAO; Shaochuan DU; Yu ZHANG (Kuangchan zonghe liyong)
This is an article in the field of mineral processing engineering. The flake graphite flotation concentrate in Madagascar was purified by hydrofluoric acid method. The grade of raw material flake graphite was 94.96%. Based on the single-factor condition tests, the purification process was established that the mixture of hydrochloric acid and hydrofluoric acid was 3.5 mL/g, HF volume fraction was 40%, and the graphite grade could be purified to 99.98% by water bath reaction at 60 ℃ for 8 h. In view of the poor purification effect of fine graphite, the graphite was screened and classification before purification. The fine graphite class was subjected to ultrasonic shock pretreatment test, and acid leaching was carried out for purification after 60 min of ultrasonic shock. After purification, the fixed carbon content of fine graphite class was ≥99.92%.